Tinjauan Akad Ijarah terhadap Denda Biaya Keterlambatan Praktik Sewa Menyewa Rental Mobil - Siti Karomah Nuraeni; Panji Adam Agus Putra; Ira Siti Rohmah Maulida (UNISBA Press, 2022)
Abstract. Late fines that appear at an additional 10% of the rental price if it exceeds the time limit, it is subject to a fine. This late penalty in the purpose of Islamic law includes usury or not, it is necessary to do research. This study aims to determine the practice of renting a late fee penalty and reviewing the ijarah contract on the rental system regarding late fee penalties at Graha Bastian car rental. The research method uses an empirical approach with qualitative methods. Based on research conducted in data collection, namely by means of observation, interviews, and documentation. Based on the research results obtained as follows: first, the practice of leasing at Graha Bastian provides additional terms and conditions in the collective agreement, namely additional fees or fines, so that when there is a delay in returning the car, a fine will be imposed according to the agreement in the written contract when making a transaction. Second, there are additional conditions in the form of late fees for tenants who default. in the review of the ijarah contract that this late penalty is not included in the accounts payable so that the imposition of fines based on syartul jaza'i in fiqh terms is allowed for the purpose of education so that there is discipline in the time of returning goods and there is a commission to cover losses to the rental owner due to negligence on the part of the lessee. The late penalty does not include usury because it is not initiated by accounts payable. Abstrak. Denda keterlambatan yang muncul pada biaya tambahan 10% dari harga sewa jika melebihi batas waktu maka dikenakan denda. Denda keterlambatan ini dalam tujuan hukum islam termasuk riba atau tidak maka perlu dilakukan penelitian. Penelitian ini bertujuan untuk mengetahui praktik sewa menyewa denda biaya keterlambatan, tinjauan akad ijarah terhadap sistem sewa menyewa mengenai denda biaya keterlambatan di graha bastian rental mobil. Metode penelitian menggunakan pendeketan empiris dengan metode kualitatif. Berdasarkan penelitian yang dilakukan dalam pengumpulan data yaitu dengan cara observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian yang diperoleh sebagai berikut: pertama, praktek sewa-menyewa di Graha Bastian memberikan tambahan syarat ketentuan pada kesepakatan bersama yaitu biaya tambahan atau denda, sehingga ketika terjadi keterlambatan pengembalian mobil akan dikenakan denda sesuai kesepakatan pada kontrak tertulis ketika melakukan transaksi. Kedua, adanya ketentuan syarat tambahan berupa denda keterlambatan bagi pihak penyewa yang melakukan wanprestasi dalam tinjauan akad ijarah bahwasannya denda keterlambataan ini tidak termasuk kedalam hutang piutang sehingga pengenaan denda dalam syartul jaza’i dalam istilah fikih itu diperbolehkan yang bertujuan untuk edukasi agar disiplinnya waktu dalam pengembalian barang dan adanya komisi untuk menutupi kerugian kepada pemilik sewa akibat kelalain dari pihak penyewa.